The indispensability of nursing actions for the elderly in times of pandemic by Covid-19 (Research, Society and Development, 2022)
Objective: to analyze the scientific evidence available in the literature about nursing actions for elderly patients with SARS-CoV-2. Methodology: this is an integrative literature review, outlined by the PICo strategy, carried out in the time frame of the years 2020 to 2022 in the LILACS and SCIELO health library databases, using the following descriptors: elderly, nursing care, and covid-19. Results: through the descriptors, a total of 661 articles were found, then, the inclusion and exclusion criteria were applied, making a final total of 08 articles. Discussion: It was identified that the pandemic of Covid-19 afflicted the health of the elderly through the high lethality evidenced in the studies, in the context of natural changes related to senescence, as well as in the processes of social isolation, implying directly in their mental health and activities of daily living. It was verified, in this lens, that nursing actions are crucial for a positive prognosis of the patient, being essential in the hospital and home environment, or even in long-stay institutions, in support of their systematized and managerial processes, through actions promotion and prevention, in line with sanitary measures, as well as health education. Conclusion: nursing undoubtedly represented in the studies as a necessary tool to minimize the perpetuation of the covid-19 pandemic, it allows, within its attributions, the resignification of this scenario and the validation of new health perspectives for the health of the elderly.